2015
DOI: 10.1080/00222895.2015.1022247
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Training at the Onset of Reaching in Preterm Infants: Randomized Clinical Trial

Abstract: The authors' aim was to investigate the immediate effect of a single specific training session (serial varied practice), of short duration on the kinematic parameters of reaching, in the period of the emergence of the skill in preterm and low birth weight infants. The study included 16 infants of both sexes, born at a mean gestational age of 32.13 (±1.36) weeks and mean birth weight of 1720.94 (±358.46) g. The infants were randomly divided into 2 groups: experimental and control. The experimental group was giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 77 publications
(127 reference statements)
0
10
1
7
Order By: Relevance
“…Although, at first glance, the observed results demonstrate numerous possibilities of responses in these younger infants, the researchers affirm that they bring valuable sensory-motor experience which is fundamental to support and drive change in development. Even young infants have shown small sporadic changes in perception and action over a short time scale, as in the study by Guimarães & Tudella 26 , which indicated that even shortterm practice may increase an infant's intrinsic motivation to reach the object, demonstrating their sensory-motor capacity to perceive and respond to the demands of the task. In this way, it might have been necessary to practice for a longer time scale for these small changes to reflect on behavioral stability, becoming more consistent.…”
Section: Discussionmentioning
confidence: 82%
“…Although, at first glance, the observed results demonstrate numerous possibilities of responses in these younger infants, the researchers affirm that they bring valuable sensory-motor experience which is fundamental to support and drive change in development. Even young infants have shown small sporadic changes in perception and action over a short time scale, as in the study by Guimarães & Tudella 26 , which indicated that even shortterm practice may increase an infant's intrinsic motivation to reach the object, demonstrating their sensory-motor capacity to perceive and respond to the demands of the task. In this way, it might have been necessary to practice for a longer time scale for these small changes to reflect on behavioral stability, becoming more consistent.…”
Section: Discussionmentioning
confidence: 82%
“…Few studies included infants at risk for developmental disorders 5,9,10,20,22 . They addressed infants born preterm or at risk for ASD.…”
Section: Which Methodological Aspects the Studies Have Been Using To mentioning
confidence: 99%
“…Most of the studies started the training before or within a few days after reaching onset, thus minimizing the influence of spontaneous practice as a confounding factor that could bias the outcomes. On the other hand, some studies did not report on the infants' skill level [21][22][23]27 , which makes it more difficult to conclude on how much the training improved reaching regardless of the influence of spontaneous practice. Future studies must be attentive to this issue.…”
Section: Which Methodological Aspects the Studies Have Been Using To mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when compared to full-term children, the exploitation of the environment becomes more difficult for the preterm infant 4,5 . In view of this; the increase in the number of premature infants is an issue that requires caution and monitoring of their development and quality of life 6,7,8 .…”
mentioning
confidence: 99%